STUDI PERANCANGAN KAPASITOR BANK 1200 KVAR DI PT. RAYA SINERGI ELEKTRIKAL - -, Listiawati; Tarigan, Amani Darma; Tarigan, Adisastra P (Politeknik Harapan Bersama Tegal, 2024)
Electricity is a vital necessity for human life, and one aspect related to electricity is the electrical panel, which functions as the distributor of electrical energy. PT. Raya Sinergi Elektrikal is a company engaged in the manufacturing of electrical panels, with one of its products being the Capacitor Bank Panel, which serves to improve power factor. The production of capacitor bank panels involves design considerations, including the components to be used, panel construction, wiring diagrams, single-line diagrams, and calculations of Capacitor Bank Panel requirements. The Capacitor Bank Panel can be operated manually or automatically. This research was conducted through direct observation and interviews at PT. Raya Sinergi Elektrikal to gather data related to the topic. This study adds new knowledge and understanding regarding the design of 1200KVAR Capacitor Bank Panels, which are widely used in industries and offices to minimize power factor losses.